Surgical damage to the lymphatic system promotes tumor growth via impaired adaptive immune response. Issue 1 (April 2018) - Nakamura, Yoshiyuki; Fujisawa, Yasuhiro; Okiyama, Naoko; Watanabe, Rei; Tanaka, Ryota; Ishitsuka, Yosuke; Tahara, Hideaki; Fujimoto, Manabu
Abstract: Background: Both lymph nodes (LNs) and lymphatic channels from primary sites to regional LNs are critical for initiation of adaptive immunity. However, as LNs are common metastatic sites in skin cancers, LN biopsies or dissections are frequently performed. In addition, reconstructive skin flaps after tumor resection may damage lymphatic flow from primary sites to regional LNs. Objective: This study was designed to investigate the effect on tumor progression by such surgeries. Methods: We developed a mouse model that simulates LNs dissection or skin flap that blocks lymphatic flow from primary sites to regional LNs and monitored tumor progression. Results: As a poor immunogenic tumor line, the growth of inoculated B16F10 melanoma into syngeneic C57BL/6 mice was not affected by these surgeries. However, the growth of the same cell line in allogenic Balb/c mice was accelerated while immune cell infiltration (CD4 + and CD8 + T cells) into the tumor was reduced by these surgeries. In addition, both cytotoxicity against B16F10 melanoma and numbers of apoptotic tumor cells were diminished by these surgeries. Similarly, tumor growth of the immunogenic MC38 cell line in syngeneic C57BL/6 mice was accelerated and immune cell infiltration and apoptotic tumor cells were reduced by these surgeries. Conclusion: These results strongly indicate that surgical damage of the lymphatic system may promote tumor progression via impaired adaptive immune response.